1980
DOI: 10.1128/iai.27.2.643-649.1980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Activated Macrophages on Nocardia asteroides

Abstract: The mechanism(s) of host resistance against Nocardia asteroides has not been well defined. Since disease due to N. asteroides frequently occurs in patients with impaired cell-mediated immunity, we studied the interaction of N. asteroides with activated and control mouse peritoneal macrophages. Activated macrophages were from mice infected with Toxoplasma gondii or injected with Corynebacterium parvum. N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Así mismo dentro de los fagocitos, es capaz de resistir los mecanismos deletéreos dependientes de oxígeno, debido a catalasas y superóxido-dismutasas que expresa 1 . Ciertas cepas bacteriales son capaces de liberarse de los macrófagos y reactivarse 30 . Dos mecanismos de sobrevivencia como la capacidad de transformarse a formas-L y la de metabolizar la fosfatasa ácida lisosomal como fuente de carbono, parecieran estar involucrados en la permanencia de las bacterias en el huésped por tiempo indefinido 1 .…”
Section: Discussionunclassified
“…Así mismo dentro de los fagocitos, es capaz de resistir los mecanismos deletéreos dependientes de oxígeno, debido a catalasas y superóxido-dismutasas que expresa 1 . Ciertas cepas bacteriales son capaces de liberarse de los macrófagos y reactivarse 30 . Dos mecanismos de sobrevivencia como la capacidad de transformarse a formas-L y la de metabolizar la fosfatasa ácida lisosomal como fuente de carbono, parecieran estar involucrados en la permanencia de las bacterias en el huésped por tiempo indefinido 1 .…”
Section: Discussionunclassified
“…The data suggested that as N. caviae grew within the host during the early stages of infection there was a cell-mediated response that involved T-lymphocytes, macrophages, and polymorphonuclear leukocytes that could effectively inhibit the growth of the organism. The organisms that were thus contained were gradually stripped of their cell wall, probably by the interaction of highly activated macrophages (8,15,16). The resulting protoplasts or spheroplasts appeared to be refractile to the milieu of degradative enzymes that were released, and the cells survived within certain tissues.…”
Section: Mice the Colonies Were Typical Of Bacterial L-mentioning
confidence: 99%
“…Nocardia asteroides also produces mycetoma and is the main etiologic agent of pulmonary nocardiosis, which causes about 500 to 1,000 cases per year in the United States (4,22). Although the pathogenic mechanisms of nocardial infections have not been completely elucidated, some authors have reported experiments indicating that the cellular immune response plays an important role in resistance (10,12). The role of the humoral immune response in nocardial infections is not well known, although some authors have observed that antibody production is associated with worsening lesions (18).…”
mentioning
confidence: 99%